Perioperative Methadone and Ketamine for Postoperative Pain Control in Spinal Surgical Patients: A Randomized, Double-blind, Placebo-controlled Trial. (17th March 2021) - Murphy, Glenn S.; Avram, Michael J.; Greenberg, Steven B.; Benson, Jessica; Bilimoria, Sara; Maher, Colleen E.; Teister, Kevin; Szokol, Joseph W.
Abstract : Background: Despite application of multimodal pain management strategies, patients undergoing spinal fusion surgery frequently report severe postoperative pain. Methadone and ketamine, which are N -methyl-d -aspartate receptor antagonists, have been documented to facilitate postoperative pain control. This study therefore tested the primary hypothesis that patients recovering from spinal fusion surgery who are given ketamine and methadone use less hydromorphone on the first postoperative day than those give methadone alone. Methods: In this randomized, double-blind, placebo-controlled trial, 130 spinal surgery patients were randomized to receive either methadone at 0.2 mg/kg (ideal body weight) intraoperatively and a 5% dextrose in water infusion for 48 h postoperatively (methadone group) or 0.2 mg/kg methadone intraoperatively and a ketamine infusion (0.3 mg · kg −1 · h −1 infusion [no bolus] intraoperatively and then 0.1 mg · kg −1 · h −1 for next 48 h [both medications dosed at ideal body weight]; methadone/ketamine group). Anesthetic care was standardized in all patients. Intravenous hydromorphone use on postoperative day 1 was the primary outcome. Pain scores, intravenous and oral opioid requirements, and patient satisfaction with pain management were assessed for the first 3 postoperative days. Results: Median (interquartile range) intravenous hydromorphone requirements were lower in the methadone/ketamine group on postoperative day 1 (2.0 [1.0 to 3.0] vs . 4.6 [3.2 to 6.6] mg in the methadone group, median difference [95% CI] 2.5 [1.8 to 3.3] mg; P < 0.0001) and postoperative day 2. In addition, fewer oral opioid tablets were needed in the methadone/ketamine group on postoperative day 1 (2 [0 to 3] vs . 4 [0 to 8] in the methadone group; P = 0.001) and postoperative day 3. Pain scores at rest, with coughing, and with movement were lower in the methadone/ketamine group at 23 of the 24 assessment times. Patient-reported satisfaction scores were high in both study groups. Conclusions: Postoperative analgesia was enhanced by the combination of methadone and ketamine, which act on both N -methyl-d -aspartate and μ-opioid receptors. The combination could be considered in patients having spine surgery. Abstract : In a randomized trial of 130 spinal surgery patients, adding ketamine to methadone reduced pain scores from 4 to 2 points on an 11-point Likert scale and roughly halved postoperative opioid use. Adding low-dose ketamine to methadone improves analgesia and reduces opioid requirement and could be considered in patients recovering from spine surgery. Supplemental Digital Content is available in the text.